Effect of Teaching Breastfeeding Technique on Breastfeeding Position in Primiparous Women - Atefeh Vafadar Miss; Fatemeh Shobiri; Seyedeh Zahra Masoumi; Younes Mohammadi (Journal of Education and Community Health)
Aims Although the body of nursing mothers naturally produces milk, breastfeeding technique should be learned and it needs teaching. Regarding the education in successful lactation process, this search was performed with the aim of investigating the effect of teaching breastfeeding technique on breastfeeding position in primiparous women. Materials & Methods In this semi–experimental study with pre-test post-test design with control group, which was conducted in 2016, 74 primiparous women referring to health centers in Hamadan were selected by multistage random cluster sampling method and randomly assigned to experimental and control groups. After completing demographic questionnaire for all samples, in days 3-5, 10, and 15 after childbirth, experimental group received teaching breastfeeding technique and control group received common educations and Bristol Breastfeeding Assessment Checklist in these days for sample was completed by researcher. The data were analyzed by 20 SPSS software, using independent t-test. Findings After the first stage of education, there was a significant difference between control and experimental groups in the sucking stage (p<0.05). Also, there was a significant difference in sucking and swallowing stages (p<0.05). In addition, total score of breastfeeding checklist showed significant difference in control and experimental groups in the first and second stages. Conclusion Teaching breastfeeding technique by standard tools in many steps and face to face can improve mothers’ breastfeeding.